2014
DOI: 10.1519/jsc.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Recovery After a Single Session of Resistance Exercise With and Without Vascular Occlusion

Abstract: The aim of this study was to investigate the heart rate variability (HRV) following resistance training with and without vascular occlusion. It was hypothesized that low intensity with vascular occlusion would elicit comparable post-exercise HRV responses to that of high intensity without vascular occlusion. Nine subjects undertook four experimental sessions of leg press exercise on different days: 1) one repetition maximum (1RM) test, 2) 4 sets of 8 repetitions + one set until exhaustion at 80% of 1RM without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 32 publications
5
31
0
6
Order By: Relevance
“…The primary results of the present study were as follows: i) the three groups exhibited increased SBP, HR and DP but did not exhibit differences on SpO2; ii) the LL and LL+BFR treatments resulted in greater hemodynamic increases compared with the HI treatment; and iii) the phases of the MC seem to influence only HR and DP. Nonetheless, we observed a significant increase in SBP, HR and DP among the three exercise groups, and between the few studies that evaluated these variables after RE with BFR (Araújo et al, 2014;Brandner, Kidgell, & Warmington, 2015;Neto et al, 2016;Okuno et al, 2014), two corroborate with our findings (Brandner et al, 2015;Neto et al, 2016). These authors reported increased SBP, DBP and MBP (Brandner et al, 2015) and HR and DP (Brandner et al, 2015;Neto et al, 2016) immediately after LL with BFR and after LL and HI exercises.…”
Section: Oxygen Saturation (Spo2)supporting
confidence: 90%
See 2 more Smart Citations
“…The primary results of the present study were as follows: i) the three groups exhibited increased SBP, HR and DP but did not exhibit differences on SpO2; ii) the LL and LL+BFR treatments resulted in greater hemodynamic increases compared with the HI treatment; and iii) the phases of the MC seem to influence only HR and DP. Nonetheless, we observed a significant increase in SBP, HR and DP among the three exercise groups, and between the few studies that evaluated these variables after RE with BFR (Araújo et al, 2014;Brandner, Kidgell, & Warmington, 2015;Neto et al, 2016;Okuno et al, 2014), two corroborate with our findings (Brandner et al, 2015;Neto et al, 2016). These authors reported increased SBP, DBP and MBP (Brandner et al, 2015) and HR and DP (Brandner et al, 2015;Neto et al, 2016) immediately after LL with BFR and after LL and HI exercises.…”
Section: Oxygen Saturation (Spo2)supporting
confidence: 90%
“…With respect to the greater increase in hemodynamics in the LL and LL+BFR groups when compared with the HI group, four studies disagree with our findings Okuno et al, 2014;Poton & Polito, 2016, 2015, and one corroborates with our findings (Araújo et al, 2014). In this context, we observed that the hemodynamics seem to significantly increase the HI protocol when compared with LL or LL+BFR in men.…”
Section: Oxygen Saturation (Spo2)supporting
confidence: 46%
See 1 more Smart Citation
“…Several studies have evaluated the acute effects of RE with BFR in isolated arms or legs on physiological variables, such as heart rate (Takano et al ., ; Renzi et al ., ; Kacin & Strazar, ; Okuno et al ., ; Vieira et al ., ), double product (DP) (Renzi et al ., ; Vieira et al ., ) and perceived exertion (Wernbom et al ., ; Loenneke et al ., ,b, ; Mendonca et al ., ; Thiebaud et al ., ; Vieira et al ., ). However, no studies have evaluated these variables using agonist–antagonist exercises in upper and lower body RE sessions with BFR.…”
Section: Introductionmentioning
confidence: 99%
“…As pesquisas mostram sua eficácia sobre variáveis neuromusculares, como os ganhos de força e hipertrofia muscular (Pearson & Hussain, 2015), hormonais (Inagaki, Madarame, Neya, & Ishii, 2011), metabólicas (Burgomaster et al, 2003;Fujita et al, 2007), hemodinâmicas (Araújo et al, 2014;Brandner, Kidgell, & Warmington, 2014;Neto et al, 2015;Neto et al, 2016;Okuno, Pedro, Leicht, Ramos, & Nakamura, 2014;Rossow et al, 2011;Vieira, Chiappa, Umpierre, Stein, & Ribeiro, 2013) e complacência arterial (Iida et al, 2011;Iida et al, 2005).…”
Section: Introductionunclassified